n ⋅ 3 x + 3 − x = 3
Determine the sum of all positive numbers n for which the equation above has a unique solution in x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good work! Yours is a algebra based solution. Mine was calculus based.
We will prove that the required numbers ' n ' are those which satisfy n ≤ 0 or n = 4 9 . Let n , x be real numbers. Let f ( x ) = 3 1 − x − 3 − 2 x .
Then n ⋅ 3 x + 3 − x = 3 ⇒ f ( x ) = n .
For all real numbers x : f ′ ( x ) = ln ( 3 ) ⋅ 3 − 2 x ( 2 − 3 1 + x ) .
Let x 0 = ln ( 3 ) ln ( 3 2 ) (that is 3 1 + x 0 = 2 ). We then have:
and since 3 1 + x 0 = 2 , we have f ( x 0 ) = 3 ⋅ 2 3 − ( 2 3 ) 2 = 4 9 .
From this, we can easily deduce that the equation f ( x ) = n has a unique solution if and only if n = f ( x 0 ) = 4 9 or n ≤ 0 . But since we need positive n , we end up with n = 4 9 = 2 . 2 5 .
Problem Loading...
Note Loading...
Set Loading...
S a t y a j i t I think I managed to find a much easier way to solve the problem without using logs. Firstly multiply the equation by 3 x then rearrange to obtain: n . 3 2 x − 3 . 3 x + 1 = 0 Now let y = 3 x : n y 2 − 3 y + 1 = 0 To obtain a unique solution for x we need a corresponding unique solution for y so the discriminant must equal zero: b 2 − 4 a c = 9 − 4 n = 0 ∴ n = 4 9 = 2 . 2 5